Neck Braces in Motocross: Different Designs and Their Effects on Muscular Activity of the Neck. (2015) - Thiele, Gerrit; Kafka, Patricia; Litzenberger, Stefan; Sabo, Anton
Abstract: Neck braces are designed to prevent traumatic injuries of the cervical spine by transferring the forces occurring at the head and spine to adjacent body structures, mainly the torso. Gorasso and Petrone (2013) showed that neck braces can influence the muscular activity of the neck during motocross riding, but their results only refer to one analysed neck brace system. Based on their results, this work analyses the effect of different neck brace designs on muscular activity of the neck during specific events in motocross riding. During on-track-measurements the muscular activity of m. sternocleidomastoideus and the upper part of m. trapezius were recorded in three different conditions: driving without neck brace (C1); driving with neck brace system A (C2); driving with neck brace system B (C2). For all the conditions mentioned the following riding events were examined: (a) turn, (b) bumps and (c) jump. Based on the results, it can be concluded that wearing a neck brace during motocross riding has various effects on the muscular activity of the neck. Depending on the neck brace design, the effects can be an increased or a decreased activity of the involved muscles and a change in the distribution of muscular activity in the neck. According to the recent results and with additional research, an improved neck brace system with optimized design can be developed, which not only serves protective purposes, but also can help to relieve the riders neck muscles during riding.